The silk weavers of Kyoto : family and work in a changing traditional industry - Hareven, Tamara K. (University of California Press, 2002)
Readers can learn firsthand how weavers perceive their craft and how they interpret their lives and view the world around them. With rare immediacy, this text captures a way of life that is repidly disappearing.